Molecular insights of fungal endophyte co-inoculation with Trichoderma viride for the augmentation of forskolin biosynthesis in Coleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Babu, C. S. Vivek (Phytochemistry, 2021)
To understand the compatibility of three native endophytic fungi Phialemoniopsis cornearis (SF1), Macrophomina pseudophaseolina (SF2) and Fusarium redolens (RF1) with Trichoderma viride (TV1) on Coleus forskohlii in enhancing plant growth and forskolin content, field experiments were conducted. Co-inoculation of RF1+TV1 showed significant improvement in plant growth (52%), root biomass (67%), and in planter forskolin content (94%), followed by treatment with SF2+TV1 and SF1+TV1. qRT-PCR was carried out to quantify expression of five key forskolin biosynthetic pathway genes (CfTPS2, CfTPS3, CfTPS4, CfCYP76AH15, and CfACT1-8) in RF1+TV1 treated C. forskohlii plants. Elevated expression of CfTPS2, CfTPS4, CfCYP76AH15 and CfACT1-8 genes was observed with RF1+TV1 combination as compared to uninoculated C. forskohlii plants. Besides, RF1+TV1 treatment considerably reduced the severity of nematode infection of C. forskohlii plants under field conditions. Thus, congruent properties of F. redolens (RF1) were witnessed with co-inoculation of T. viride (TV1) under field conditions which resulted in enhanced forskolin content, root biomass, and reduced nematode infections in C. forskohlii. Overall, this approach could be an economical and sustainable step towards cultivation of commercially important medicinal plants.
Keywords: Co-inoculation; Coleus forskohlii; endophytes; Forskolin; Lamiaceae; Trichoderma viride